PENERAPAN TEKNOLOGI INFORMASI BAGI PELAKSANAAN PELAYANAN PUBLIK (STUDI KASUS PADA BP2TSP KOTA SAMARINDA) - Zul Fahlefi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The aims of this article is to describe about the application of information technology in order to conduct data management for public service in BP2TSP of Samarinda city. The result shows that an application of information technology was run well through both program and application according to data structure for licensing service internally. But the program operators still need mentoring process by software support provider. Furthermore it still needs to be expanded for increasing effectiveness of coordination and cooperation with the other related institution externally.